Chromatic aberration in the Black-necked Stilt, Himantopus mexicanus, in Ceará, Brazil - Rabêlo, Lucas Tavares; Sales Junior, Luís Gonzaga; de Oliveira, Thaís Pereira; Crozariol, Marco Aurélio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
An individual of Himantopus mexicanus with aberrant plumage was observed on November 10, 2020 and again on March 3, 2021 between the municipalities of Fortaleza and Eusébio, Ceará, Brazil. The specimen was among a group of birds of the same species and it had leucism or progressive greying, this being the first documented record of chromatic aberration for the genus Himantopus in South America.
Keywords: Recurvirostridae; Atypical coloration; Leucism; Progressive greying